Covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst as well as preparation method and application thereof
By constructing a surface-to-surface contact Z-type heterojunction photocatalyst between two-dimensional CTF and two-dimensional Ag/TiO2 nanosheets, the problem of high photogenerated charge recombination rate and insufficient CO2 catalytic reaction sites during photocatalytic CO2 reduction was solved, and efficient CO2 catalytic reaction activity and cycle stability were achieved.
Patent Information
- Application Number
- CN202411990292.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
Smart Images

Figure BDA0005223508320000081 
Figure BDA0005223508320000091 
Figure HDA0005223508360000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic CO2 reduction, and in particular to a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst, and a preparation method and application thereof. Background Art
[0002] The massive consumption of fossil fuels in industrial production has caused a sharp increase in the greenhouse gas CO2 content in the atmosphere, triggering a series of global problems such as climate warming and glacier melting. How to effectively reduce the CO2 content in the atmosphere has become a difficult problem that humans urgently need to solve. Inspired by plant photosynthesis, photocatalytic CO2 reduction technology can use abundant solar energy as a driving force to convert CO2 into high-value-added chemicals such as CO and CH3OH under mild conditions. It is one of the most promising means to achieve CO2 resource utilization.
[0003] The development of new and efficient photocatalysts is the key to improving the performance of photocatalytic CO2 reduction systems. Among the many semiconductor photocatalytic materials, covalent organic framework materials are crystalline materials with topological structures formed by connecting organic monomers through covalent bonds. Among them, the two-dimensional triazine-based covalent organic framework (CTF) has shown many advantages in the field of photocatalysis due to its unique morphology and electronic structure: 1) the ordered conjugated structure and layered stacked π orbitals have excellent light absorption and photogenerated charge migration capabilities; 2) the uniform and adjustable open pores and high specific surface area can enhance the adsorption and mass transfer capabilities of CO2; 3) it has high structural controllability and chemical stability. Therefore, CTF has become an ideal platform for improving the efficiency of photocatalytic CO2 reduction and exploring the reaction mechanism. However, studies have found that the photogenerated charge recombination rate of this material is high during the photocatalytic CO2 reduction process, and the CO2 catalytic reaction sites in the CTF composed of non-metallic elements C and N are insufficient, resulting in slow reaction kinetics, which seriously restricts its catalytic reaction efficiency and large-scale practical application. Therefore, the rational design of two-dimensional CTF-based photocatalysts to achieve a significant improvement in photocatalytic CO2 reduction activity is of great significance for alleviating energy and environmental problems. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst and its preparation method and application. The photocatalyst provided by the present invention can improve the separation and transfer efficiency of photogenerated electrons and holes in CTF, and has excellent CO2 catalytic reaction activity and stability.
[0005] Compared with the prior art, the present invention provides a novel covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst and a preparation method and application thereof. The photocatalyst provided by the present invention is firstly prepared by combining a two-dimensional triazine-based covalent organic framework material with a two-dimensional Ag / TiO2 nanosheet through electrostatic self-assembly, and then heating it at 200-350°C in an inert gas atmosphere to enhance the interface interaction and introduce nitrogen vacancies to obtain a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst; and the two-dimensional triazine-based covalent organic framework material is prepared by a mixed reaction of 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3; it is found through experiments that the photocatalyst provided by the present invention can not only improve the separation and transfer efficiency of photogenerated electrons and holes in CTF, but also reduce the energy barrier of CO2 reduction reaction, promote CO2 adsorption and activation ability, and thus show excellent CO2 catalytic reaction activity and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 This is a schematic diagram of the preparation process of the covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst of the present invention;
[0007] Figure 2 Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images of (ac) Ag / TiO2, (d) CTF-Nv and (ef) TiO2 / Ag / CTF-Nv;
[0008] Figure 3 Transmission electron microscope element distribution map of TiO2 / Ag / CTF-Nv.
[0009] Figure 4 X-ray diffraction patterns (XRD) of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv photocatalysts;
[0010] Figure 5 Fourier transform infrared spectra (FT-IR) of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv photocatalysts;
[0011] Figure 6 Zeta potential diagram of Ag / TiO2 and CTF;
[0012] Figure 7 Electron paramagnetic resonance spectra (EPR) of TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv;
[0013] Figure 8UV-visible diffuse reflectance images of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv;
[0014] Fig. 9 (a) Photocatalytic CO2 reduction performance test of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv and (b) Cyclic stability test of TiO2 / Ag / CTF-Nv;
[0015] Fig.10 Photoelectrocatalytic performance of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv (a) time-current (IT) curve, (b) electrochemical impedance spectroscopy (EIS) curve;
[0016] Fig.11 The photocatalytic CO2 reduction performance comparison chart of TiO2 / Ag / CTF-Nv, TiO2 / Ag / CTF-Nv-200 and TiO2 / Ag / CTF-Nv-300;
[0017] Fig.12 The photocatalytic CO2 reduction performance comparison chart of TiO2 / Ag / CTF-Nv, TiO2 / Ag / CTF-Nv-(1:2.3) and TiO2 / Ag / CTF-Nv-(1:0.43);
[0018] Fig.13 Band gap diagram of TiO2 and CTF-Nv;
[0019] Fig.14 Mott-Schottky plot of TiO2 and CTF-Nv;
[0020] Fig.15 Schematic diagram of the energy band structure of TiO2 / Ag / CTF-Nv;
[0021] Fig.16 Electron paramagnetic resonance spectra of TiO2 / Ag / CTF-Nv (a) DMPO-·OH- and (b) DMPO-·O 2- ;
[0022] Fig.17 Schematic diagram of the Z-type charge transfer mechanism in the photocatalytic CO2 reduction process of TiO2 / Ag / CTF-Nv. DETAILED DESCRIPTION
[0023] The present invention provides a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst, which is composited with a two-dimensional CTF and a two-dimensional Ag / TiO2 nanosheet by electrostatic self-assembly, and then heated at 200-350°C in an inert gas atmosphere to obtain a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst;
[0024] The two-dimensional CTF is prepared by a mixed reaction of 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3.
[0025] According to the present invention, the covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst of the present invention is prepared by compounding two-dimensional CTF with two-dimensional Ag / TiO2 nanosheets, and then heating to 200-350°C in an inert gas atmosphere to react to obtain a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst; wherein the mass ratio of the two-dimensional CTF to the two-dimensional Ag / TiO2 nanosheets is preferably 1:(0.25-4), more preferably 1:(1-3); the reaction temperature is preferably 250-300°C, and the inert gas atmosphere is preferably a nitrogen atmosphere; the compounding is preferably dispersing the two-dimensional CTF and the two-dimensional Ag / TiO2 nanosheets in distilled water, ultrasonically mixing them evenly, and evaporating the water to obtain a two-dimensional CTF and two-dimensional Ag / TiO2 nanosheet composite.
[0026] In the present invention, the two-dimensional CTF is prepared by a mixed reaction of 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3. The molar ratio of the 1,4-benzenedimethanol, the 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and the Cs2CO3 is 1:(0.50-0.80):(2.0-2.8), and more preferably 1:(0.66-0.70):(2.2-2.4); the mixed reaction is preferably adding 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3 to dimethyl sulfoxide, and then reacting at 95-105°C for 22-26 hours after ultrasonic dispersion, and then reacting at 160-190°C for 22-26 hours, cooling, washing and drying to obtain a two-dimensional CTF material, wherein the washing is preferably washing the cooled material with hydrochloric acid, distilled water, ethanol and tetrahydrofuran in sequence to obtain the washed two-dimensional CTF.
[0027] In the present invention, the two-dimensional Ag / TiO2 nanosheets are preferably obtained according to the following preparation method:
[0028] Tetrabutyl titanate and 47% HF aqueous solution are mixed to react to obtain a white solid powder, and the white powder is calcined in an air atmosphere muffle furnace at 440-460° C. for 2-4 hours to obtain a two-dimensional TiO2 nanosheet;
[0029] TiO2 nanosheets and AgNO3 are dispersed in a solvent at a mass ratio of 1:(0.0079-0.031) and mixed to react to obtain two-dimensional Ag / TiO2 nanosheets. The solvent is preferably a mixture of methanol and water, and the volume ratio of water to methanol is preferably (5-6):1; the reaction is preferably carried out in an inert gas atmosphere, and the reaction method is preferably carried out by photodeposition method using 300W xenon lamp irradiation.
[0030] The present invention also provides a method for preparing a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst, comprising compounding a two-dimensional triazine-based covalent organic framework material with a two-dimensional Ag / Tio2 nanosheet through electrostatic self-assembly, and then heating and reacting at 200-350°C in an inert gas atmosphere to obtain a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst; wherein the two-dimensional triazine-based covalent organic framework material is prepared by a mixed reaction of 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3. The preferred embodiment of the preparation method is the same as the method defined in the above-mentioned covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst.
[0031] The present invention also provides a carbon dioxide photoreduction reaction, wherein the photocatalyst of the carbon dioxide photoreduction reaction is the covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst described in the present invention.
[0032] The present invention also provides a photoelectrode, wherein the photocatalyst in the photoelectrode is the covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to any one of claims 1 to 7.
[0033] The covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst provided by the present invention is a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst containing N vacancies in face-to-face contact by combining a two-dimensional triazine-based covalent organic framework material with a two-dimensional Ag / TiO2 nanosheet using a method of electrostatic self-assembly and inert atmosphere annealing. The unique face-to-face contact, reasonable energy band structure, and fast interface charge transfer channel (Ag) between the two-dimensional CTF and the TiO2 nanosheet in the material will help increase the interface contact area, shorten the charge transfer distance, and promote the transfer and separation of photogenerated electrons and holes. At the same time, the CTF with a porous structure and rich in N vacancies is conducive to promoting the adsorption and activation of CO2. When the material is used for the photocatalytic CO2 reduction reaction, under simulated sunlight irradiation, the material exhibits an excellent CO generation rate of 74.98 μmol h -1 g -1, which is much higher than TiO2, CTF-Nv and other materials. In addition, the quantum efficiency of TiO2 / Ag / CTF-Nv can reach 0.89% at a wavelength of 400nm, and after four cycle stability tests, the CO generation rate remains basically unchanged, showing high cycle stability.
[0034] The following will be described clearly and completely in conjunction with the technical solutions of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] Step S1: Preparation of two-dimensional triazine-based covalent organic framework material: 1.0 mmol of 1,4-benzenedimethanol, 0.66 mmol of 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and 2.4 mmol of Cs2CO3 were added to the dried dimethyl sulfoxide solution in sequence, and ultrasonically dispersed for 0.5 h to obtain a light yellow suspension. The solution was then heated in a constant temperature oil bath at 100°C for reaction for 24 h, and the color of the suspension turned orange. The temperature was continued to rise to 180°C for reaction for 36 h, and then naturally cooled to room temperature to obtain a brick-red suspension. The solid sample was separated by filtration, and washed step by step with hydrochloric acid, distilled water, ethanol and tetrahydrofuran in sequence to wash away the residual Cs2CO3 and unreacted organic monomers in the product. After drying, a yellow two-dimensional triazine-based covalent organic framework material was obtained, recorded as CTF.
[0037] Step S2: Preparation of two-dimensional Ag / TiO2 nanosheets: 5mL of tetrabutyl titanate was fully stirred and dissolved in 1mL of 47% HF to obtain a light yellow oil solution. The solution was then placed in a hydrothermal reactor and sealed, heated at 200°C for 24h, and naturally cooled to room temperature. The solid sample was centrifuged, washed with distilled water, and vacuum dried at 60°C for 10h to obtain a white powder. It was heated to 450°C at a rate of 5°C / min in a muffle furnace under air atmosphere, and calcined at this temperature for 2h to obtain a two-dimensional TiO2 nanosheet. Subsequently, 50mg of two-dimensional TiO2 nanosheets and 0.8mg of AgNO3 were added to 60mL of 10% methanol aqueous solution in sequence. After ultrasonic dispersion, it was placed in a closed quartz reactor. After the internal air was exhausted by Ar gas, the reaction solution was irradiated with a 300W xenon lamp for 0.5h using a photodeposition method. After the reaction was completed, white two-dimensional Ag / TiO2 nanosheets were obtained by centrifugation, washing, and drying.
[0038] Step S3: Covalent organic framework-based all-solid-state Z-type photocatalytic material: The two-dimensional CTF and the two-dimensional Ag / TiO2 nanosheets are dispersed in distilled water at a mass ratio of 1:1, and after ultrasonic dispersion for 1 hour, a yellow suspension is obtained, and then the solution is placed in an 80°C constant temperature oil bath for heating and stirring until the water is completely evaporated to obtain a yellow solid powder. After sufficient grinding, it is calcined at 250°C in a nitrogen atmosphere tube furnace for 2 hours, and the heating rate is 2°C / min to enhance the interface interaction and introduce N vacancies. After cooling to room temperature, the solid sample is collected to obtain a two-dimensional sheet-like stacked covalent organic framework-based all-solid-state Z-type photocatalytic material rich in N vacancies, which is recorded as TiO2 / Ag / CTF-Nv.
[0039] The process flow chart for preparing the covalent organic framework-based all-solid-state Z-type photocatalytic material is as follows: Figure 1 As shown, Figure 1 This is a schematic diagram of the preparation process of the covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst described in the present invention.
[0040] Example 2
[0041] In this embodiment, two-dimensional Ag / TiO2 nanosheets and two-dimensional CTF are prepared in the same manner as in Example 1, except that in step S3, the two-dimensional CTF is not annealed after being composited with the Ag / TiO2 nanosheets, and finally a covalent organic framework-based all-solid-state Z-type photocatalytic material is obtained, which is recorded as TiO2 / Ag / CTF.
[0042] Example 3
[0043] In this embodiment, two-dimensional CTF and two-dimensional Ag / TiO2 nanosheets are prepared in the same manner as in Example 1, except that in step S3, the annealing temperature after the two-dimensional CTF and Ag / TiO2 nanosheets are composited is 200°C, and finally a covalent organic framework-based all-solid-state Z-type photocatalytic material is obtained, which is recorded as TiO2 / Ag / CTF-Nv-200.
[0044] Example 4
[0045] In this embodiment, two-dimensional CTF and two-dimensional Ag / TiO2 nanosheets are prepared in the same manner as in Example 1, except that in step S3, the annealing temperature after the two-dimensional CTF and Ag / TiO2 nanosheets are composited is 300°C, and finally a covalent organic framework-based all-solid-state Z-type photocatalytic material is obtained, which is recorded as TiO2 / Ag / CTF-Nv-300.
[0046] Example 5
[0047] In this embodiment, two-dimensional CTF and two-dimensional Ag / TiO2 nanosheets are prepared in the same manner as in Example 1, except that in step S3, the mass ratio of two-dimensional CTF to Ag / TiO2 nanosheets is 1:2.3, and finally a covalent organic framework-based all-solid-state Z-type photocatalytic material is obtained, which is recorded as TiO2 / Ag / CTF-Nv-(1:2.3).
[0048] Example 6
[0049] In this embodiment, two-dimensional CTF and two-dimensional Ag / TiO2 nanosheets are prepared in the same manner as in Example 1, except that in step S3, the mass ratio of two-dimensional CTF to Ag / TiO2 nanosheets is 1:0.43, and finally a covalent organic framework-based all-solid-state Z-type photocatalytic material is obtained, which is recorded as TiO2 / Ag / CTF-Nv-(1:0.43).
[0050] Example 7
[0051] Step S1: Preparation of two-dimensional triazine-based covalent organic framework material: 1.0 mmol of 1,4-benzenedimethanol, 0.66 mmol of 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and 2.4 mmol of Cs2CO3 were added to the dried dimethyl sulfoxide solution in sequence, and ultrasonically dispersed for 0.5 h to obtain a light yellow suspension. The solution was then heated in a constant temperature oil bath at 100°C for reaction for 24 h, and the color of the suspension turned orange. The temperature was continued to rise to 180°C for reaction for 36 h, and then naturally cooled to room temperature to obtain a brick-red suspension. The solid sample was separated by filtration, and washed step by step with hydrochloric acid, distilled water, ethanol and tetrahydrofuran in sequence to wash away the residual Cs2CO3 and unreacted organic monomers in the product. After drying, a yellow two-dimensional triazine-based covalent organic framework material was obtained, recorded as CTF.
[0052] Step S2: Preparation of two-dimensional TiO2 nanosheets: 5 mL of tetrabutyl titanate was fully stirred and dissolved in 1 mL of 47% HF to obtain a light yellow oil solution. The solution was then sealed in a hydrothermal reactor, heated at 200°C for 24 hours, and naturally cooled to room temperature. The solid sample was centrifuged, washed with distilled water, and vacuum dried at 60°C for 10 hours to obtain a white powder. The mixture was heated to 450°C at a rate of 5°C / min in a muffle furnace under an air atmosphere, and calcined at this temperature for 2 hours to obtain a two-dimensional TiO2 nanosheet.
[0053] Step S3: Covalent organic framework-based all-solid Z-type photocatalytic material: The two-dimensional CTF and the two-dimensional TiO2 nanosheets are dispersed in distilled water at a mass ratio of 1:1, and after ultrasonic dispersion for 1 hour, a yellow suspension is obtained, and then the solution is placed in an 80°C constant temperature oil bath for heating and stirring until the water is completely evaporated to obtain a yellow solid powder. After sufficient grinding, it is calcined at 250°C in a nitrogen atmosphere tube furnace for 2 hours, and the heating rate is 2°C / min to enhance the interface interaction and introduce N vacancies. After cooling to room temperature, the solid sample is collected to obtain a two-dimensional sheet-stacked covalent organic framework-based Z-type photocatalytic material rich in N vacancies, which is recorded as TiO2 / CTF-Nv.
[0054] Example 8 Testing of samples
[0055] The Ag / TiO2, CTF and TiO2 / Ag / CTF-Nv photocatalysts in Example 1 were tested by transmission electron microscopy (TEM). Figure 2 . Figure 2 Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images of (ac) Ag / TiO2, (d) CTF-Nv and (ef) TiO2 / Ag / CTF-Nv; Figure 2 It can be seen from the figures marked a and d that both TiO2 and CTF exhibit two-dimensional nanosheet structures, and Ag nanoparticles of uniform size have been modified on the TiO2 surface. Figure 2 In the HRTEM images marked b and c, it can be seen that the lattice spacing of the TiO2 nanosheet is 0.38nm, confirming that it is the (100) crystal plane of anatase TiO2. The lattice spacing of the Ag nanoparticle is 0.28nm, and its exposed surface is the (110) crystal plane. Figure 2 As shown in the figures marked e and f, Ag / TiO2 nanosheets are modified on the two-dimensional amorphous CTF in a face-to-face stacking manner. Figure 3 The transmission electron microscope element distribution diagram of TiO2 / Ag / CTF-Nv further shows the composite structure formed by Ag / TiO2 and CTF. Figure 1 to Figure 3 The results all confirmed the successful construction of two-dimensional surface-to-surface contact TiO2 / Ag / CTF-Nv heterojunction.
[0056] In order to further confirm the catalyst structure, the inventors conducted X-ray diffraction test analysis and Fourier transform infrared spectroscopy analysis on the catalysts in Example 1 and Example 6. The test results are as follows: Figure 4-5 shown. Figure 4 X-ray diffraction patterns (XRD) of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv photocatalysts; Figure 5 Fourier transform infrared spectra (FT-IR) of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv photocatalysts; Figure 4 The characteristic diffraction peaks of the TiO2 sample in the sample again confirm that it belongs to the anatase structure, and CTF also shows obvious characteristic diffraction peaks. The diffraction peaks of anatase TiO2 and CTF exist simultaneously in TiO2 / Ag / CTF-Nv and TiO2 / CTF-Nv, confirming that the two semiconductors have been combined to form a heterogeneous structure. However, the characteristic diffraction peaks of Ag were not observed, which may be due to the highly uniform dispersion and small size of the Ag particles. In addition, Figure 5 As shown, the Fourier transform infrared spectra of TiO2 / Ag / CTF-Nv and TiO2 / CTF-Nv contain the characteristic absorption peaks of TiO2 and CTF, which also confirms the formation of heterogeneous structure.
[0057] In order to explore the mechanism of heterojunction formation, the surface charges of TiO2, Ag / TiO2 and CTF were tested using Zeta potential. The experimental results are shown in Figure 6 . Figure 6 The Zeta potential diagram of Ag / TiO2 and CTF is shown in the figure. It can be seen from the figure that Ag / TiO2 has a positive surface charge and the CTF surface has a negative charge. During the composite process of the two, due to the existence of electrostatic interaction, the positive and negative charges attract each other to form a TiO2 / Ag / CTF heterojunction.
[0058] In order to confirm the formation of nitrogen vacancies in CTF, the TiO2 / Ag / CTF-Nv and TiO2 / Ag / CTF catalysts prepared in Example 1 and Example 2 were subjected to electron paramagnetic resonance spectroscopy (EPR) analysis to obtain Spectrum 7. Figure 7 is the electron paramagnetic resonance spectrum (EPR) of TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv; Figure 7 It can be seen that there is almost no electron spin signal in TiO2 / Ag / CTF, and TiO2 / Ag / CTF-Nv has an obvious electron spin signal at g=2.005, indicating that after calcination in an inert gas atmosphere, N vacancies can be introduced into CTF, thereby changing the electronic structure of CTF and promoting CO2 adsorption and activation.
[0059] To explore the effect of the unique Z-type heterostructure on the light absorption ability of CTF, UV-visible diffuse reflectance spectroscopy has been tested. Figure 8 UV-visible diffuse reflectance graphs of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv; Figure 8 As shown, compared with pure CTF-Nv and TiO2 / Ag / CTF, the unique TiO2 / Ag / CTF-Nv photocatalytic material exhibits slightly increased light absorption, indicating that the construction of heterojunction and nitrogen vacancies can enhance the light absorption of CTF. In a closed quartz reactor, under simulated sunlight, the prepared photocatalysts TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CT and TiO2 / Ag / CTF-Nv were tested for photocatalytic CO2 reduction performance to explore the effects of the unique Z-type heterostructure and N vacancies on the photocatalytic CO2 reduction performance. The specific operations are as follows:
[0060] 5 mg of photocatalyst was dispersed in 200 μL of deionized water and ultrasonically treated for 30 min. The obtained suspension was placed on a sample stand. After drying at 60 °C, the sample stand was placed in a closed reactor containing 20 mL of water. No sacrificial reagents or photosensitizers were added. Subsequently, high-purity CO2 gas was introduced into the reactor for 20 min. The light source was a 300 W xenon lamp, and the reaction temperature was controlled at 10 °C by circulating cooling water. Every 30 min, 0.5 mL of gas was taken with a 1 mL gas injection needle and injected into a gas chromatograph (GC, Shimadzu GC2014) for qualitative and quantitative analysis and detection of gas products.
[0061] The results are as follows Fig. 9 As shown, Fig. 9 (a) Photocatalytic CO2 reduction performance test and (b) Cyclic stability test of TiO2 / Ag / CTF-Nv for TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv, TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv; Fig. 9 As can be seen in the figure a, the CO generation rate of pure CTF-Nv is only 15.65 μmol g -1 h -1 When TiO2 and CTF are combined to form a TiO2 / CTF-Nv heterojunction, the CO generation rate can reach 34.90 μmol g -1 h -1 , indicating that the heterostructure can effectively increase the charge utilization rate and improve the CO2 reduction activity. By introducing Ag nanoparticles charge transfer channel at the TiO2 / CTF-Nv heterointerface, the charge transfer and separation will be further promoted, and the CO yield will be significantly improved to 74.98μmol g -1 h -1, which is more than 4.6 times the activity of pure CTF. By comparing the photocatalytic CO2 reduction activity of TiO2 / Ag / CTF and TiO2 / Ag / CTF-Nv, the effect of N vacancies on CO2 reduction was investigated. The test showed that the CO yield of TiO2 / Ag / CTF without nitrogen vacancies was 38.05 μmol g -1 h -1 , which is lower than that of TiO2 / Ag / CTF-Nv, proving that the construction of N vacancies can effectively improve the CO2 reduction activity. In addition, excellent cycle stability and durability are extremely important for the practical application of catalysts. Fig. 9 The cycle stability test results of TiO2 / Ag / CTF-Nv in part b show that after 4 cycles of testing, the CO yield of the material remained basically unchanged and still maintained a high activity, which indicates that TiO2 / Ag / CTF-Nv has extremely high photocatalytic stability and practical application potential. Therefore, by loading Ag / TiO2 nanosheets on the surface of two-dimensional CTF to construct a face-to-face contact Z-type heterojunction and introducing N vacancies, it is an effective method to improve the photocatalytic CO2 reduction activity of CTF, which is far superior to most similar photocatalytic materials reported.
[0062] The comparison of CO2 reduction activity of the photocatalyst prepared by the present invention and the catalyst reported in the literature is shown in Table 1.
[0063] Table 1
[0064]
[0065]
[0066] In addition, we also designed the prepared photocatalytic material into a photoelectrode for photoelectrocatalytic testing to explore its photogenerated charge separation and transfer capabilities. Preparation and testing of photoelectrode: Weigh 5 mg of photocatalyst and ultrasonically disperse it in a mixed solution of 2 mL of anhydrous ethanol and 0.5 mg of polyvinylidene fluoride to form a uniform colloidal dispersion. Then take 50 μL of the dispersion and evenly drop it on an area of 1 cm 2 The photoelectrode was prepared by drying the surface of fluorine-doped SnO2 transparent conductive glass (FTO) at 60℃ for 2h. The photoelectrocatalytic test was carried out in a standard three-electrode system, in which the FTO with the photocatalyst drop-coated was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The light source was a 300W xenon lamp, and the electrolyte solution was 0.5mol L -1 The test voltage of the time-current (IT) curve is 0.62V (vs.Ag / AgCl). The electrochemical impedance spectroscopy (EIS) is at 0.62V (vs.Ag / AgCl) and the 5 The test was conducted in a frequency range of Hz.
[0067] The results are as follows Fig.10 As shown, Fig.10 The photoelectrocatalytic performance of TiO2, Ag / TiO2, CTF-Nv, TiO2 / CTF-Nv and TiO2 / Ag / CTF-Nv is (a) time-current curve (IT), (b) electrochemical impedance spectroscopy (EIS); Fig.10 Part a of the figure shows the time-current curves of different photoanode materials. RHE Under bias, TiO2 / Ag / CTF-Nv exhibits the highest photocurrent density, which can reach 2.8 μA cm -2 , which is much higher than the other samples, indicating that it has excellent charge separation and transfer capabilities and high carrier concentration. In addition, from the AC impedance spectrum ( Fig.10 From the analysis of the part b of Figure 1, we can see that compared with CTF-Nv, TiO2 / CTF-Nv and TiO2 / Ag / CTF samples, TiO2 / Ag / CTF-Nv has a smaller arc radius, indicating that it has a smaller charge transfer resistance (R ct ). Therefore, the above results all confirm that the unique Z-type heterostructure and abundant nitrogen vacancies of the new TiO2 / Ag / CTF-Nv photocatalytic material can effectively promote charge separation and transfer and improve the utilization rate of photogenerated charges.
[0068] Fig.11 The photocatalytic CO2 reduction performance comparison diagram of TiO2 / Ag / CTF-Nv, TiO2 / Ag / CTF-Nv-200 and TiO2 / Ag / CTF-Nv-300 in Examples 1, 3 and 4 is shown in the figure. As can be seen from the figure, TiO2 / Ag / CTF-Nv exhibits the highest CO generation rate, indicating that the content of N vacancies generated at 250°C is optimal, which can maximize the CO2 activation ability. Fig.12 This is a comparison chart of the photocatalytic CO2 reduction performance of TiO2 / Ag / CTF-Nv, TiO2 / Ag / CTF-Nv-(1:2.3) and TiO2 / Ag / CTF-Nv-(1:0.43) in Examples 1, 5 and 6. The figure shows that when the ratio of CTF-Nv and Ag / Tio2 is 1:1, the constructed heterostructure has the best activity, and increasing or decreasing the content of CTF-Nv may increase the probability of charge recombination. Fig.13 The band gap diagram of TiO2 and CTF-Nv semiconductors. Based on the UV-visible diffuse reflectance test results, it is calculated that the band gap of TiO2 is 3.16eV and the band gap of CTF-Nv is 2.38eV. In addition, based on Fig.14According to the Mott-Schottky test results, the conduction band positions of TiO2 and CTF-Nv are -0.32eV and -0.78eV respectively. Therefore, based on the band gap and conduction band position, we can determine the energy band structure diagram of TiO2 / Ag / CTF-Nv heterojunction ( Fig.15 ). Fig.16 This is the in-situ electron paramagnetic resonance spectrum (EPR) of TiO2 / Ag / CTF-Nv. Fig.16 As shown in a, no hydroxyl radical generation was detected in the CTF-Nv sample during the photocatalytic process. Both TiO2 and TiO2 / Ag / CTF-Nv were able to generate hydroxyl radicals during the photocatalytic reaction, and the TiO2 / Ag / CTF-Nv material was able to generate more hydroxyl radicals. Fig.16 As shown in (b), only TiO2 / Ag / CTF-Nv and CTF-Nv can detect superoxide radical signals during the photocatalytic reaction. Therefore, by combining the analysis of the band structure of TiO2 and CTF-Nv and the in situ EPR results, we can confirm that the transport of photogenerated electrons and holes in TiO2 / Ag / CTF-Nv is a Z-type mechanism. The specific charge transfer process, such as Fig.17 As shown in the figure, when light is irradiated on the TiO2 / Ag / CTF-Nv heterojunction, TiO2 and CTF-Nv are simultaneously excited to generate electrons and holes. Due to the reasonable band structure position, the conduction band electrons of TiO2 will be transferred to the valence band position of CTF-Nv through the intermediate charge transfer channel (Ag) to recombine with holes, leaving electrons and holes with higher reaction activity in CTF-Nv and TiO2 respectively. In addition, CTF-Nv with abundant N vacancies can further increase CO2 activation, and finally obtain efficient photocatalytic CO2 reduction activity.
[0069] In summary, the unique face-to-face nitrogen vacancy-rich Z-type heterojunction of the TiO2 / Ag / CTF-Nv photocatalyst exhibits efficient charge separation and transfer and excellent CO2 activation ability, thereby achieving extremely high photocatalytic CO2 reduction activity and cyclic stability.
[0070] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst, which is a two-dimensional triazine-based covalent organic framework material and a two-dimensional Ag / TiO2 nanosheet composited by electrostatic self-assembly, and then heated at 200-350°C in an inert gas atmosphere to obtain a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst; in, The two-dimensional triazine-based covalent organic framework material is prepared by a mixed reaction of 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3.
2. The covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to claim 1, characterized in that: The mass ratio of the two-dimensional triazine-based covalent organic framework material to the two-dimensional Ag / TiO2 nanosheet is 1:(0.25-4).
3. The covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to claim 1, characterized in that: The method for compositeing the two-dimensional triazine-based covalent organic framework material and the two-dimensional Ag / TiO2 nanosheet is specifically as follows: dispersing the two-dimensional triazine-based covalent organic framework material and the two-dimensional Ag / TiO2 nanosheet in distilled water, mixing them evenly by ultrasonication, heating while stirring, and evaporating the water to obtain a composite of the two-dimensional triazine-based covalent organic framework material and the two-dimensional Ag / TiO2 nanosheet.
4. The covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to claim 1, characterized in that: The molar ratio of the 1,4-benzenedimethanol, the 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and the Cs2CO3 is 1:(0.50-0.80):(2.0-2.8).
5. The covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to claim 1, characterized in that: The two-dimensional triazine-based covalent organic framework material is prepared by a mixed reaction of 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3, specifically by adding 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3 into dimethyl sulfoxide, and then reacting at 95-105° C. for 22-26 hours after ultrasonic dispersion, and then reacting at 160-190° C. for 22-26 hours, and then cooling, washing and drying to obtain the two-dimensional triazine-based covalent organic framework material.
6. The covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to claim 1, characterized in that: The preparation steps of the two-dimensional Ag / TiO2 nanosheets are as follows: Tetrabutyl titanate and 47% HF solution were mixed and reacted to obtain a white solid powder, and the white powder was calcined in an air atmosphere muffle furnace at 440-460° C. for 2-4 hours to obtain a two-dimensional TiO2 nanosheet; TiO2 nanosheets and AgNO3 are dispersed in a solvent at a mass ratio of 1:(0.0079-0.031) to react and obtain two-dimensional Ag / TiO2 nanosheets.
7. The covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to claim 6, characterized in that: The solvent is a mixture of methanol and water.
8. A method for preparing a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst, comprising: compounding a two-dimensional triazine-based covalent organic framework material with a two-dimensional Ag / TiO2 nanosheet by electrostatic self-assembly, and then heating the reaction at 200-350°C in an inert gas atmosphere to obtain a covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst; in, The two-dimensional triazine-based covalent organic framework material is prepared by a mixed reaction of 1,4-benzenedimethanol, 1,4-benzenedicarboxylic acid amide hydrochloride (1:2) and Cs2CO3.
9. A carbon dioxide photoreduction reaction, characterized in that: The photocatalyst for the carbon dioxide photoreduction reaction is the covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to any one of claims 1 to 7.
10. A photoelectrode, characterized in that: The photocatalyst in the photoelectrode is the covalent organic framework-based all-solid-state Z-type heterojunction photocatalyst according to any one of claims 1 to 7.
Citation Information
Cited By
Flue gas carbon dioxide capture and methanation catalytic material as well as preparation method and application thereof
CN121892226A